KARAKTERISTIK PERILAKU BELANJA ONLINE ANTAR GENERASI Y, Z, DAN ALPHA - Tiara Febriani; Adim Falakhi; Masita Hapsari; Alex Fahrur Riza (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Rapid technological developments have spread to all aspects of human life, one of which is the economic sector. This growth has encouraged diversity in shopping patterns among different age groups born in different eras. This study aims to describe and compare the characteristics of online shopping behavior among Millennials, Generation Z, and Generation Alpha. This study focuses on four indicators: platform preferences, shopping motivations, payment methods, and brand loyalty. The research method uses a descriptive quantitative approach. Data was collected through an online questionnaire distributed to respondents from the three generations. The use of e-commerce as a place for online shopping is motivated by cheaper prices and features such as promos, discounts, and so on. In terms of payment methods, Cash on Delivery (COD) is the preferred choice for all generations. The findings of this study show that online shopping characteristics between generations have several similarities, but there are differences in the level of platform usage and brand loyalty.